Properties of montmorillonite-reinforced thermoplastic sago starch composites - Ahmad, Zuraida; Yusof, Yusliza; Omar, Nurizan; Anuar, Hazleen; Halim, Zahurin; Samat, Noorasikin (2011)

(untitled)
In this work, biodegradable polymer was prepared from thermoplastic sago starch (TPSS) plasticized with glycerol. In order to improve the properties of the TPSS, Montmorillonite (MMT), a kind of reinforced additive was used in the preparation of montmorillonite-reinforced thermoplastic sago starch (MTRSS) composites via hot pressing method. The fabricated samples were investigated through X-ray diffractometry, Fourier transform infrared (FT-IR) as well as thermal and morphological properties. FT-IR patterns show that in the MTRSS composites, the C-O groups of sago starch molecules shifted to higher wave number, while the reactive hydroxyl groups of MMT shifted to the lower wavenumber. On the other hand, X-ray diffraction revealed that MMT restrained the crystallization of MTRSS and intercalated in TPSS. Thermogravimetric analysis (TGA) revealed that the thermal stability of MTRSS was better than those of TPSS. In addition, the scanning electron micrograph results show that MMT were uniformly dispersed in the TPSS.